Penerapan Intervensi Gratitude Journal pada Pasien Light Chain Amyloidosis dengan Risiko Bunuh Diri: Studi Kasus - Sihombing, Yulia; Idaman Wati Hulu, Hasrat; Gresia Waruwu, Ike; Tifani Simangunsong, Imala; Sihombing, Ratna (Pustaka Galeri Mandiri, 2026)
Light Chain Amyloidosis is a serious, chronic, progressive disease that causes multisystem disorders and physical weakness. Individuals with Amyloidosis face physical, financial, and psychological burdens lead to hopelessness, anxiety, and depression and even an increased risk of suicide. An intervention that can be used to help prevent the risk for suicide is Gratitude Journal. This study employed a single-case study design involving a patient with light chain amyloidosis with the nursing diagnosis “risk for suicide.” Monitoring was conducted before and after the intervention over a three-day period using the following instruments: the Patient Health Questionnaire-9 (PHQ-9), as well as the patient’s verbal expressions regarding suicidal ideation, suicidal threats, and suicide plans. Results: The intervention resulted in a decrease in the PHQ-9 score from 26 to 25, indicating an improvement in the category of “feeling unmotivated to do anything”; there were no verbal expressions of suicidal ideation, suicidal cues, suicidal threats, or suicide plans. The Gratitude Journal intervention was administered over three days through the development of a therapeutic relationship, education, Gratitude Journal writing, and daily evaluation. Patients demonstrated positive responses, including the ability to identify things for which they could still be grateful, greater openness in expressing their feelings, and an increase in life expectancy. Gratitude Journal has the potential as a simple and easily implementable psychosocial-spiritual nursing intervention to help increase gratitude, life expectancy, and psychological well-being in patients who are at risk of suicide. Consistent use of Gratitude Journal is necessary to achieve optimal results.